Is Turkey Ready for the Post COVID-19 World Order? - BAYRAKTAR, BORA (SETA Foundation, 2021)
The COVID-19 outbreak has had a huge impact on the global economy and politics. Closures and lockdowns stopped international trade resulting in an economic slowdown. It has changed the daily lives of people and the way business takes place. Politics has also been affected by the pandemic. Discussions about the changing world order have gained a new dimension and momentum. In this article, the impact of the COVID-19 pandemic in international relations is analyzed. Has COVID-19 triggered a change in the world order? If it has, what are the nature, scope, and content of this change? As a rising regional power in the Eastern Mediterranean region, how has Turkey been affected by this, and how did it respond to the changing situation? Signs of deteriorating world order, declining U.S. leadership, escalating geopolitical competition amongst global powers were in the air before the pandemic. Turkey's adaptation to this new world order pre-dates the pandemic, when it changed its political system, and invested in its security and cohesion.
Keywords: New World Order; COVID-19; Turkey; U.S.; Russia; China; Eastern Mediterranean